2022
DOI: 10.3389/fpsyt.2022.876413
|View full text |Cite
|
Sign up to set email alerts
|

Social Touch, Social Isolation, and Loneliness in Borderline Personality Disorder During the COVID-19 Pandemic

Abstract: BackgroundInterpersonal impairments in borderline personality disorder (BPD) are characterised by a lack in the sense of belonging and the fear of being excluded. One feature of interactions that can promote a sense of social belonging is interpersonal touch. While some studies suggest that individuals with BPD experience social touch as less pleasurable than healthy individuals (HCs), there are no studies that investigated whether this difference is associated with feeling less socially connected. This questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 90 publications
0
5
0
3
Order By: Relevance
“…Researchers have demonstrated that individuals with borderline personality disorder symptoms are likely to have preoccupied or fearful insecurity and hypersensitive reactions, making them less effective at handling interpersonal stress [ 63 ]. This evidence was notably demonstrated during the COVID-19 pandemic, where physical and social distancing measures were applied [ 64 ]. Such feelings of insecurity and loneliness render these individuals longing for support and emotional and social closeness.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that individuals with borderline personality disorder symptoms are likely to have preoccupied or fearful insecurity and hypersensitive reactions, making them less effective at handling interpersonal stress [ 63 ]. This evidence was notably demonstrated during the COVID-19 pandemic, where physical and social distancing measures were applied [ 64 ]. Such feelings of insecurity and loneliness render these individuals longing for support and emotional and social closeness.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2). A reduced importance of social touch for relationships, less need for and liking of social touch, as well as feelings of loneliness have been observed in patients with borderline personality disorder who also experienced significantly more childhood maltreatment than healthy controls (Schulze et al, 2022).…”
Section: Consequencesmentioning
confidence: 99%
“…Os textos completos dos estudos elegíveis foram revistos e, quando possível, extraídos os seguintes dados: autor, pais, desenho de estudo, título, objetivos, tipo de terapia, resultados e limitações. Características dos estudos incluídos Dos estudos incluídos, cinco eram quantitativos [16 -20], um transversal [21], dois casos controle [22,23] e um misto [24]. Quanto a origem dos estudos, três foram realizados na Austrália [19,21,24], um na Holanda [16], um na Espanha [18], um na Suíça [17], um na Noruega [20] e um na Alemanha [22].…”
Section: Extração De Dadosunclassified